Having fun and thriving: The impact of fun human resource practices on employees' autonomous motivation and thriving at work - Han, Xue; Li, Yuhui; Li, Jie (Human Resource Management, 2024)
AbstractResearch interest in thriving at work has burgeoned over the past decades, but little is known about how human resource (HR) practices affect employees' thriving at work. Drawing upon self‐determination theory and person‐organization fit theory, we developed and tested a moderated mediation model to explain how fun HR practices influence employees' thriving at work. The results of two studies, a scenario experiment (N = 164) and a time‐lagged survey (N = 253), supported our hypotheses. Specifically, the findings revealed that fun HR practices relates positively to employees' thriving at work. Autonomous motivation partially mediates the abovementioned relationship. Furthermore, fun HR practices translate into higher autonomous motivation and subsequent thriving at work for employees with higher preference for workplace fun. Our research contributes to the existing literature by identifying fun HR practices as an antecedent of thriving at work and revealing the psychological mechanisms through which fun HR practices affect employees' thriving at work. The practical implications, limitations, and future research avenues are also discussed.